I’m working through Adams Calculus a Complete Course ninth edition; on page 19 the parabola with focus point F(0,p) and directrix y=-p is given as 4py = x^2, the vertex is (0,0).

I was wondering what the focus point and directrix of a general parabola ax^2+bx+c would be. So I took pen and paper for an interlude.

First realise that 4p(y-k) = (x-h)^2 has (h,k) as vertex. Writing ax^2+bx+c in the form of 4p(y-k)=(x-h)^2 will help us find its focus point, directrix and vertex, all expressed in a, b and c.

\begin{aligned} y &=a x^{2}+b x+c \\ y-c &=a x^{2}+b x \\ \frac{y-c}{a} &=x^{2}+\left(\frac{b}{a}\right) x \\ \frac{y-c}{a}+\left(\frac{b}{2 a}\right)^{2} &=x^{2}+\left(\frac{b}{a}\right) x+\left(\frac{b}{2 a}\right)^{2} \\ \frac{1}{a} \left(y-c+\frac{b^{2}}{4 a}\right) &=\left(x+\frac{b}{2 a}\right)^{2} \\ 4 \cdot \underbrace{\frac{1}{4 a}}_{p} (y-\underbrace{\left(c-\frac{b^{2}}{4 a}\right)}_{k}) &=(x-\underbrace{\left(\frac{-b}{2 a}\right)}_{h})^{2} \end{aligned}

If you don’t understand the adding of \left(\frac{b}{2a}\right)^2, just think of x^2+6x+9 = (x+3)^2, where 9 = \left(\frac{6}{2}\right)^2.

The focus point is:

\begin{aligned} (h, k+p) &=\left(-\frac{b}{2 a}, c-\frac{b^{2}}{4 a}+\frac{1}{4 a}\right) \\ &=\left(-\frac{b}{2 a}, c+\frac{1-b^{2}}{4 a}\right) \end{aligned}

The directrix is:

\begin{aligned} y &=k-p \\ &=c-\frac{b^{2}}{4 a}-\frac{1}{4 a} \\ &=c-\frac{1+b^{2}}{4 a} \end{aligned}

The vertex is (h,k) = \left(-\frac{b}{2 a}, c-\frac{b^{2}}{4 a}\right).

The distance between the focal point and the vertex is p, which is \frac{1}{4a}. Why would you want to know this? Because you might want to know where to put the pan in the solar oven, or the light bulb in a parabola shaped mirror. The funny thing is that a mathematician might be interested in it just because it is possible to calculate this distance, so for no practical reason.

Just in case that you wonder if it is wright that 4p(y-k) = (x-h)^2 is a parabola with (h,k) as vertex. Let us take focus point (h,k+p) and line y=k-p, now let us see where the points (x,y) are that have the same distance to the line and the focus point:

\begin{aligned} \sqrt{(x-x)^{2}+(y-(k-p))^{2}} &= \sqrt{(x-h)^{2}+(y-(k+p))^{2}} \\ \left(\sqrt{(x-x)^{2}+(y-(k-p))^{2}}\right)^2 &= \left(\sqrt{(x-h)^{2}+(y-(k+p))^{2}}\right)^2 \\ (x-x)^{2}+(y-(k-p))^{2} &= (x-h)^{2}+(y-(k+p))^{2} \\ 0^{2}+(y-(k-p))^{2} &= (x-h)^{2}+(y-(k+p))^{2} \\ y^2-2(k-p)y+(k-p)^2 &= (x-h)^{2}+y^2-2(k+p)y+(k+p)^2  \\ -2(k-p)y+(k-p)^2 &= (x-h)^{2}-2(k+p)y+(k+p)^2 \\ -2ky +2py +k^2-2kp+p^2 &= (x-h)^{2} -2ky -2py +k^2 +2kp+p^2 \\ 2py -2kp &= (x-h)^{2} -2py +2kp \\ 2py +2py -2kp -2kp &= (x-h)^{2} \\ 4py - 4kp &= (x-h)^{2} \\ 4p(y - k) &= (x-h)^{2} \end{aligned}

About olikilo

happy, satisfied, studious, (let) do, reach, tech, different, Dominika, kids, CEO of Sue (infra & open source gurus)
This entry was posted in Calculus and tagged , , , . Bookmark the permalink.

Leave a Reply

Fill in your details below or click an icon to log in: Logo

You are commenting using your account. Log Out /  Change )

Twitter picture

You are commenting using your Twitter account. Log Out /  Change )

Facebook photo

You are commenting using your Facebook account. Log Out /  Change )

Connecting to %s